Reduction and Speciation of Monoglycerides to Produce High Quality Biodiesel - Rapaka, Srikanth (Université d'Ottawa / University of Ottawa, 2012)
Biodiesel is rapidly growing as a fuel of interest due to the various advantages it has over conventional diesel fuel. While the pros – non-toxic, biodegradable, low green house gas emissions seem advantageous, the major issue that plagues the use of biodiesel is its cold weather operability. Biodiesel can present challenges in cold-weather operation, because certain of its constituent compounds can form precipitates in the fuel. These precipitates can cause undesired effects like plugging of fuel filters and deposits. This issue has been attributed to the presence of impurities (mostly saturated monoglycerides, di-glycerides, soap etc) in biodiesel and has been discussed in the literature. There is a move by users and standards associations to implement more stringent norms and quality control to avoid problems in the widespread use of biodiesel. This study involves ways to reduce MG’s in biodiesel by mitigating to a greater extent the possibility of side reactions (formation of soap). The effect of selective transesterification of oil as a function of alcohol, temperature and catalyst concentration was also studied. Although saturated MG’s with high melting points are a greater source of deposits, it can be hypothesized that the polymorphic nature of unsaturated Monoglycerides could also be contributing to cold flow issues. It is hence vital to make sure the biodiesel is free from all forms of monoglycerides. It was also seen that there is very little specificity of selection of fatty acid types in the transesterification reaction and that the amount and type of MGs present in the biodiesel is reflected by the relative amount of fatty acids types present in the oil. In biodiesel derived from Canola oil, a preponderance of monoolein was found for all runs. The initial runs carried out as a two stage process using the membrane followed by batch reactor gave very low MG concentrations, well below ASTM standards.
Keywords: monoglycerides; elution; cold flow; biodiesel; multi stage; membrane reactor